Tamayo y Szyszlo: identidad nacional y universalismo a través de las formas - Cotrina Zegarra, Julio César (2023)
The article aims to compare, from a formal analysis, certain works by Rufino Tamayo and Fernando de Szyszlo that evoke the original national past to demonstrate in which cases the links with the subject in question are supported by plastic elements. Thus, through the analysis of the work “Aztlan” with which Tamayo illustrates a novel of the same title and of a work by Szyszlo belonging to the “Cajamarca” series, based on the poem Apu Inca Atawallpaman (The death of the Inca Atahualpa), It is intended to compare how each artist approaches the texts that allude to the history before the arrival of the Spaniards in America. Likewise, two paintings will be analyzed, one by each artist, made in the oil technique to recognize how both artists link the theme of the works with the visual elements through the same material.